2018
DOI: 10.1002/chem.201800609
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Coordinate Boron(III) and Diboron(II) Dications

Abstract: The enhanced electron-donor properties of the bulky bisimino ligand 1,2-(L N) -C H (1; L =1,3-bis(mesityl)-imidazolin-2-ylidene), mesityl=2,4,6-trimethylphenyl) were exploited for the stabilization of elusive electron-deficient and low-coordinate boron dication species. The reaction of 1 with PhBBr or (B(Cl)NMe ) afforded a dicationic mononuclear boron(III) complex or a dicationic dinuclear boron(II) complex, respectively (4 , 6 ). The bonding situations of 4 and 6 were examined by means of single crystal X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 101 publications
3
43
0
1
Order By: Relevance
“…[30] Two years later Inoue et al reported a higher yield synthesis of another representative 10 with a strongly πelectron donating bisguanidine ligand stabilizing the electron deficient boron centers ( Figure 2). [31] However, considerable allocation of positive charge into the bisimino substituent as well as the NMe 2 groups lower the boron-centered electrophilicity thus mitigating its Lewis acidity.…”
Section: Diboranes With Sp 2 -Hybridized Boron Atomsmentioning
confidence: 99%
“…[30] Two years later Inoue et al reported a higher yield synthesis of another representative 10 with a strongly πelectron donating bisguanidine ligand stabilizing the electron deficient boron centers ( Figure 2). [31] However, considerable allocation of positive charge into the bisimino substituent as well as the NMe 2 groups lower the boron-centered electrophilicity thus mitigating its Lewis acidity.…”
Section: Diboranes With Sp 2 -Hybridized Boron Atomsmentioning
confidence: 99%
“…[6,97,102] Theb icyclic guanidinate substituent hpp efficiently delocalizes the positive charge,t hereby enabling the stabilization of highly positively charged cationic boranes (enriching the field of cationic boron compounds currently being intensively studied [90,91,[106][107][108][109][110][111] ). [6,97,102] Theb icyclic guanidinate substituent hpp efficiently delocalizes the positive charge,t hereby enabling the stabilization of highly positively charged cationic boranes (enriching the field of cationic boron compounds currently being intensively studied [90,91,[106][107][108][109][110][111] ).…”
Section: Discussionmentioning
confidence: 99%
“…As econd example for at hree-coordinateb oron dication complex salt was presentedb yo ur group in 2018 (45[A n ] 2 ; with A n = Br,A lBr 4 ;F igure 13). [68] Theb is(imino) group that constitutest he ligand in 30 + ,a sw ell as 31 + was implementedt o stabilizet he cationic boronc enter.I nterestingly, 45[Br] 2 was converted to am onocation with af our-coordinate metalloid center (i.e.,b oronium ion 46 + )u pon reaction with Li[BH 4 ] (note: 46 + was also independently synthesized by conversion of bis(iminiumtosylate) with Li[PhBH 3 ], Figure 13). This sug- Figure 13.…”
Section: Two-coordinate Boron Complexes With One Cationic Charge Per mentioning
confidence: 99%
“…Ah ighery ield synthesis of at hree-coordinate diboron(II) dication complex salt (60[SbCl 6 ] 2 )w as described by ourg roup and we implementedastrongly p-electron donating bis(imino) system for thermodynamic stabilizationo ft he p-acidic boron centers (Figure17). [68] Substantiala llocationo fpositivec harge density intot he ligand was diagnosed by theoretical,a sw ella s structurala nalysis.T he mean CÀN imino bond length of 1.37 correspondst ot he dication complex 45 2 + (vide supra) andt he MBO for each of theset wo bondsa mounts to 1.17( MBO = Mayer BondI ndex). This accounts for considerables ingle-bond character of thei mino nitrogen-carbonb onds as illustratedb y ther esonance structure 60 A 2 + (i.e., ligand-centeredb oron cation, Figure 17).…”
Section: Dicationic Complexesw Ith Two M-bridged Boron(iii) Centersmentioning
confidence: 99%
See 1 more Smart Citation